2005
DOI: 10.1007/bf03166999
|View full text |Cite|
|
Sign up to set email alerts
|

Solid-state magnetic resonance studies of polyaniline as a radical scavenger

Abstract: The first detailed study of polyaniline (PANI) and reduced PANI (R-PANI) before and after reaction with the stable organic free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) by using solidstate 13C CP MAS (cross-polarization magic-angle spinning), NQS (nonquaternary suppressed) and CPPI (cross-polarization phase inversion) nuclear magnetic resonance teehniques is reported. These techniques reveal relatively subtle structural changes that occur upon reaction with DPPH free radicals and confirm the radical scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…The peaks obtained to various carbons in the P(ANI‐2NA4ABA) structure are given in Figure B. The peak positions obtained for polyaniline at 113.1, 124.1, 138.9, 140.9, 147.5 and 155.1 ppm are due to PANI, which are in accordance with the solid‐state spectrum of PANI base reported by Zujovic et al The remaining peaks are due to carbon of the 2NA4ABA, which was confirmed from 13 C analysis using ChemDraw (PerkinElmer) software. Thus, 13 C spectrum supports the formation of P(ANI‐2NA4ABA).…”
Section: Resultsmentioning
confidence: 99%
“…The peaks obtained to various carbons in the P(ANI‐2NA4ABA) structure are given in Figure B. The peak positions obtained for polyaniline at 113.1, 124.1, 138.9, 140.9, 147.5 and 155.1 ppm are due to PANI, which are in accordance with the solid‐state spectrum of PANI base reported by Zujovic et al The remaining peaks are due to carbon of the 2NA4ABA, which was confirmed from 13 C analysis using ChemDraw (PerkinElmer) software. Thus, 13 C spectrum supports the formation of P(ANI‐2NA4ABA).…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of the doped PANI sample is relatively broad in comparison with its dedoped form, revealing heterogeneity in the sample and significant charge distribution, i.e., the local variations in charge density along the polymer backbone. [25,[44][45][46] Typical PANI peaks are seen at 163.4 ppm assigned to imine quinoid carbon (C-7 in Scheme 1). However, this is shifted 3-6 ppm downfield compared to the peak obtained from a standard PANI sample, [25,44] which could be due to distortion of the structure by possible hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…[25,[44][45][46] Typical PANI peaks are seen at 163.4 ppm assigned to imine quinoid carbon (C-7 in Scheme 1). However, this is shifted 3-6 ppm downfield compared to the peak obtained from a standard PANI sample, [25,44] which could be due to distortion of the structure by possible hydrogen bonds. The peak at 146.3 ppm (C-1, attached to an imine nitrogen) is assigned to a benzenoid carbon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations